Wavelet analysis and HHG in nanorings: their applications in logic gates and memory mass devices. Issue 4 (14th December 2015) - Cricchio, Dario; Fiordilino, Emilio
Abstract : We study the application of one nanoring driven by a laser field in different states of polarization in logic circuits. Abstract : We study the application of one nanoring driven by a laser field in different states of polarization in logic circuits. In particular we show that assigning Boolean values to different states of the incident laser field and to the emitted signals, we can create logic gates such as OR, XOR and AND. We also show the possibility of making logic circuits such as half-adder and full-adder using one and two nanorings respectively. Using two nanorings we made the Toffoli gate. Finally we use the final angular momentum acquired by the electron to store information and hence show the possibility of using an array of nanorings as a mass memory device.